Root Systems in Lie Theory: From the Classic Definition to Nowadays - Angiono, Iván Ezequiel (2024)
The purpose of this article is to discuss the role played by root systems in the theory of Lie algebras and related objects in representation theory, with focus on the combinatorial description and properties.